Visuality of M. Elizarov’s Novels “Librarian” and “Cartoons” as a Means of Transforming Socialist Realist Canon - I. R. Kuryaev; E. P. Ovsyannikova (Научный диалог, 2024)
This article examines the role of the visual aspect of the text in the recontextualization of elements from the socialist realist canon. The study focuses on Mikhail Elizarov’s novels “Librarian” and “Cartoons.” It is established that, firstly, Elizarov consciously constructs his works according to the principles of literary cinematicity, with visuality serving as a prominent component. Secondly, visuality facilitates the integration of elements from the Soviet project into the narrative, expressed through spaces and objects. Furthermore, it allows for their recontextualization by embedding them within new contexts. Thirdly, the reactivation of spaces and objects is aided by the figure of the protagonist, who is presented through the technique of traveling. Fourthly, the narrative development of the novels bears similarities to socialist realist plots concerning re-education. Additionally, through the image of the protagonist, the relevance of the opposition between “eye” and “gaze” is emphasized, which in turn contributes to the actualization of ideas related to control and behavior modeling. The gaze of the Other, experienced by the characters, draws them into narrative structures akin to those found in socialist realism, compelling them to adopt specific roles — the role of a character burdened with socialist realist motives. Finally, it is noted that the protagonist’s distinctive position enhances reader identification and alters the very status of the Book.